2015
DOI: 10.1002/mc.22437
|View full text |Cite
|
Sign up to set email alerts
|

miR‐211 and MITF modulation by Bcl‐2 protein in melanoma cells

Abstract: Melanoma, the most lethal form of skin cancer, is frequently associated with alterations in several genes, among which the Bcl-2 oncogene plays an important role in progression, chemosensitivity and angiogenesis. Also microRNA (miRNA) are emerging as modulators of melanoma development and progression, and among them, miR-211, located within the melastatin-1/TRPM1 (transient receptor potential cation channel, subfamily M, member 1 protein) gene, is prevalently expressed in the melanocyte lineage and acts as onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 47 publications
4
21
0
Order By: Relevance
“…Finally, using public microarray and RNA-seq databases of human melanoma patient specimens, we found that there is a positive correlation between bcl-xL and CXCL8 expression, confirming the evidence obtained in vitro with human melanoma cell lines. 4 Indeed, in melanoma specimens, bcl-xL expression correlated with markers of aggressiveness: MITF, a survival factor in melanocytes and melanoma, 45 frequently amplified in this kind of tumor 46 and recently described as being regulated by bcl-xL homolog bcl-2, 47 and SOX10, which promotes primary melanoma and its metastatization 48 and recently proposed as a promising new serum marker for detection of early stage melanoma. 49 Interestingly, it was confirmed that bcl-xL overexpression is able to enhance MITF and SOX10 expression in human melanoma cells and that this increase is counteracted by CXCL8 secretion inhibition.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, using public microarray and RNA-seq databases of human melanoma patient specimens, we found that there is a positive correlation between bcl-xL and CXCL8 expression, confirming the evidence obtained in vitro with human melanoma cell lines. 4 Indeed, in melanoma specimens, bcl-xL expression correlated with markers of aggressiveness: MITF, a survival factor in melanocytes and melanoma, 45 frequently amplified in this kind of tumor 46 and recently described as being regulated by bcl-xL homolog bcl-2, 47 and SOX10, which promotes primary melanoma and its metastatization 48 and recently proposed as a promising new serum marker for detection of early stage melanoma. 49 Interestingly, it was confirmed that bcl-xL overexpression is able to enhance MITF and SOX10 expression in human melanoma cells and that this increase is counteracted by CXCL8 secretion inhibition.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study demonstrated that expression of miR-211 increased after down-regulating the level of Bcl-2 [47]. The Bcl-2 expression up-regulated in tissues after transfection of miR-21 mimics and expression of Bax, apoptosis, caspase-3 activity, and the chemosensitivity decreased, indicating miR-21 could promote Bcl-2 expression by combining with the 3′-UTR of Bcl-2 [48].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported Bcl-2 ability to regulate the expression of miR-211 and miR-204, two miRNA involved in melanoma progression and resistance 2 . To evaluate whether the expression of miR-378a-5p was modulated by Bcl-2, we used either Bcl-2 overexpressing clones previously obtained and characterized 2 , or melanoma cells in which Bcl-2 expression was silenced by siRNA 2 . Increased miR-378a-5p expression was found in M14 and A375 cells overexpressing Bcl-2 ( Fig.…”
Section: Bcl-2 Modulation Affects Mir-378a-5p Expressionmentioning
confidence: 99%